Parental supply of alcohol and alcohol consumption in adolescence: prospective cohort study. Issue 2 (5th October 2016) - Mattick, R. P.; Wadolowski, M.; Aiken, A.; Clare, P. J.; Hutchinson, D.; Najman, J.; Slade, T.; Bruno, R.; McBride, N.; Degenhardt, L.; Kypri, K.
Abstract : Background: Parents are a major supplier of alcohol to adolescents, yet there is limited research examining the impact of this on adolescent alcohol use. This study investigates associations between parental supply of alcohol, supply from other sources, and adolescent drinking, adjusting for child, parent, family and peer variables. Method: A cohort of 1927 adolescents was surveyed annually from 2010 to 2014. Measures include: consumption of whole drinks; binge drinking (>4 standard drinks on any occasion); parental supply of alcohol; supply from other sources; child, parent, family and peer covariates. Results: After adjustment, adolescents supplied alcohol by parents had higher odds of drinking whole beverages [odds ratio (OR) 1.80, 95% confidence interval (CI) 1.33–2.45] than those not supplied by parents. However, parental supply was not associated with bingeing, and those supplied alcohol by parents typically consumed fewer drinks per occasion (incidence rate ratio 0.86, 95% CI 0.77–0.96) than adolescents supplied only from other sources. Adolescents obtaining alcohol from non-parental sources had increased odds of drinking whole beverages (OR 2.53, 95% CI 1.86–3.45) and bingeing (OR 3.51, 95% CI 2.53–4.87). Conclusions: Parental supply of alcohol to adolescents was associated with increased risk of drinking, but not bingeing. These parentally-supplied children also consumed fewer drinks on a typical drinking occasion. Adolescents supplied alcohol from non-parental sources had greater odds of drinking and bingeing. Further follow-up is necessary to determine whether these patterns continue, and to examine alcohol-related harm trajectories. Parents should be advised that supply of alcohol may increase children's drinking.